An investigation of binary surfactant in the synthesis of gold nanorods. Issue 3 (April 2021) - Wei, Ming-Zhang; Deng, Tian-Song; Zhang, Qi; Gu, Yi-Jie; Cheng, Zhiqun
Abstract: The method by using hexadecyltrimethylammonium bromide (CTAB) and sodium oleate (NaOL) as binary surfactant mixture to synthesize high quality gold nanorods (AuNRs) has been one of the most widely used methods in this field. But the specific influence on the obtained AuNRs of these two surfactants has not been systematically studied in previous works. Here, we carry out series of experiments and characterized the results. By using the UV-VIR spectrophotometer and transmission electron microscope, we found the higher CTAB concentrations will lead to the larger aspect ratios of the obtained AuNRs. In addition, the final products under this method are more sensitive to the NaOL concentration.